Organizational structure, capacity and reach of organizations involved in alcohol prevention: An assessment of stakeholders across five countries in East Africa - Raderalazasoa, Gina U.; Swahn, Monica H.; Balenger, Adelaide; Kalema, David; Mukantabana, Crescence; Komba, Sophia; Rukundo, Aloysius; Okwarah, Patrick (International Journal of Alcohol and Drug Research, 2024)
Aims: East African countries, classified as low- and middle-income countries (LMICs), are disproportionately harmed by alcohol consumption, and many countries lack strategies to address and prevent alcohol harm. This study draws on community input from stakeholders involved in alcohol harm prevention in five East African countries to identify organizational structures, capacity and outreach, and strategies for capacity building to address the high burden of alcohol harm more systematically. Design/Setting/Participants: A cross-sectional survey was distributed from October to December 2020 by the East Africa Alcohol Policy Alliance to their member alliances and stakeholders across five countries in East Africa (i.e., Burundi, Kenya, Rwanda, Tanzania and Uganda). Analyses were based on 171 persons from 171 organizations completing the survey. Measures: The East Africa Alcohol Policy Alliance Capacity Assessment Survey (EAAPACAS) included organizational size and funding, research capacity, priorities, and perceptions related to alcohol prevention and harm locally and nationally. Results: The types of organizations, funding structures, and functions dedicated to alcohol prevention vary widely across countries, indicating great diversity and heterogeneity of organizations working on alcohol prevention and advocacy in East Africa. Most organizations rely on volunteer staff. Additionally, 51% reported that they did not know, or could not meet their program goals, with the available operational funds. Conclusion: These organizations rely primarily on volunteers and face significant barriers to achieving their goals with their current budget, primarily derived from foundations and private donations. Overall, these findings indicate that the infrastructure for alcohol prevention is weak and fragmented in countries where national initiatives are limited or underfunded.
Keywords: Organizational structure; Alcohol prevention; Stakeholders; East African countries